VOLATILITAS HARGA SAHAM DI INDONESIA DAN MALAYSIA - Andi Kartika (AMIK Jakarta Teknologi Cipta Semarang, 2008)
Disintermediatior phenomena in financial market show that many people tend to invest in capital market more than in banking. That is happened, because of the return on stock is profitable than banking interest rate. But, there is a big risk in capital market. It is natural, financial market that high risk high return, low risk low return. So, if we do not want to loss, we must have ability to analyze stock performance, specially volatility of stock. This research use to ARCH/GARCH model to estimation of volatility. The research show that stock growth in 2007 2009 tend to decrease for all index (JSX and KLCI). JSX and KLCI just have ARCH effect, so the index influence volatility this time price index. The research show too that a value = 0,7 and sum of a and b almost one for all index (JSX and KLCI). That are means, the volatilit stocks are persistent or the volatility are high and persistent.Keywords : ARCH, GARCH, volatility and persistent